Just climate urbansims: Aligning U.S. municipal policy with national movements for climate justice - Jones, Peyton. (Tufts University. Tisch Library., 2023)
Thesis (M.A.)--Tufts University, 2023.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisors: Kathryn Davies, and Penn Loh.; Keywords: Climate change, Urban planning, and Environmental justice.